Pengaruh Badan Usaha Milik Desa (Bumdes) Terhadap Kesejahteraan Masyarakat Di Desa Pandansari Kecamatan Sine Kabupaten Ngawi - Sangrila Puspita Dewi (Universitas Merdeka Madiun, 2020)
The objectives of this study are (1) to describe the Village Owned Enterprises (BUMDES) in Pandansari Village, Sine District, Ngawi Regency; (2) to describe the Community Welfare in Pandansari Village, Sine District, Ngawi Regency; (3) to determine the influence of Village-Owned Enterprises (BUMDES) on Community Welfare in Pandansari Village, Sine District, Ngawi Regency. The population in this study were residents or community members who were members of the Bansdes Pandansari Village, Sine District, Ngawi Regency, amounting to 75 people. Data collection techniques in this study were questionnaires and documentation. While the data analysis techniques in this study are quantitative descriptive analysis, simple regression analysis and hypothesis testing (t test). The findings of this study are (1) Village-Owned Enterprises (BUMDES) in Pandansari Village, Sine District, Ngawi Regency are classified as good; (2) Community Welfare in Pandansari Village, Sine District, Ngawi Regency is classified as Good; (3) There is an influence of Village-Owned Enterprises (BUMDES) on Community Welfare in Pandansari Village, Sine District, Ngawi Regency.Â Keywordsâ€”: village-owned enterprise; community welfare.